Strategi Pengembangan Pariwisata Pesisir untuk Optimalisasi Potensi Daerah di Kabupaten Aceh Besar - Ikhbar, Samsul; Sufriadi, Dedi; Islami, Putri Dian; Ridara, Rina; Sunaya, Cut (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the development strategy of the coastal tourism industry in Aceh Besar Regency in order to optimize regional potential. Aceh Besar Regency has a variety of rich beach tourism potential, but it has not been fully utilized to support regional economic growth and community welfare. The research method used is qualitative descriptive with a field study approach, through observation, interviews, and the dissemination of questionnaires to the community, business actors, and beach tourism visitors. The analysis is focused on the existing conditions of coastal tourism, development strategies that can be carried out, as well as supporting and inhibiting factors in the process of optimizing regional potential. The results of the study show that the optimization of beach tourism potential can be achieved through improving the quality of infrastructure, strengthening destination promotion, developing a creative economy based on local communities, and applying environmental sustainability principles. With the right strategy, the development of the coastal tourism industry in Aceh Besar Regency has the potential to make a significant contribution to regional development and improving community welfare.